Parents, homework and socio-economic class: Discourses of deficit and disadvantage in the "new" South Africa - Felix, Nadine; Dornbrack, Jacqui; Scheckle, Eileen (English teaching : practice and critique, 2008)
It has been claimed that homework is an effective means of developing good study habits (Cooper, 1994) and fostering positive attitudes (Marzano & Pickering, 2007) and self-responsibility (Brown, in Plato, 2000). If we are to believe this, then we need to ensure that all learners have equal or at least similar opportunities to gain these advantages. However, it seems unlikely in the Republic of South Africa, given the history of discrimination and deliberate under-funding of specific schools during apartheid. In order to discover in what ways and how schools in different socio-economic situations manage homework, we designed a multiple case study of three primary schools in the Eastern Cape. Since we could not assume that homework formed a regular part of the daily activities, we interviewed the principals and Grade 4 teachers of each school. This paper discusses the discourses of the teachers and principals and particularly the language used by them when discussing parents and homework. The study found that parents from the school situated in a more affluent area were ascribed agency and power, whereas parents from poorer socio-economic groups were positioned as disinterested and unable to assist their children. Such discourses reproduce deficit notions and practices resulting in further inequalities.